2021
DOI: 10.1182/blood.2021011677
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno mini virus as a cause of childhood acute promyelocytic leukemia lacking PML/RARA fusion

Abstract: Astolf et al provide the first report of acute promyelocytic leukemia driven by viral insertion into the RARA locus. This represents a clear demonstration of a pathology driven by the member of the anelloviruses, a group of viruses otherwise thought to have minimal or no pathogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…The detailed treatment and outcome of the 3 patients are shown in Table 1. Transplantation was rarely used as a modality for vAPL, given the short-term followup and small number of the cases, but the benefit has been discussed in some variants with the high relapse rate, like STAT5B-RARA (9) and very young cases, like TTMV-RARA (7). Our patient had even stronger indications for transplantation due to complicated chromosome karyotype and poorly prognostic mutated genes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The detailed treatment and outcome of the 3 patients are shown in Table 1. Transplantation was rarely used as a modality for vAPL, given the short-term followup and small number of the cases, but the benefit has been discussed in some variants with the high relapse rate, like STAT5B-RARA (9) and very young cases, like TTMV-RARA (7). Our patient had even stronger indications for transplantation due to complicated chromosome karyotype and poorly prognostic mutated genes.…”
Section: Discussionmentioning
confidence: 89%
“…The outcome seems to be suboptimal in a number of cases with poor response to ATRA and ATO, such as ZBTB16-RARA. Still, fusions, such as NPM1-RARA and FIP1L1-RARA, are sensitive to ATRA, and fusions, such as TTMV-RARA, are sensitive to both ATRA and ATO combination therapy (4,7). Generally, these variants should be treated with a combination of ATRA and chemotherapy (anthracyclines), with the possible use of AML protocols in known resistant variants (4,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, viral reads were detected in 1346 (72.0%) cases. Particularly prevalent were torque teno viruses, which are extremely common in humans 24 and have very recently been implicated in a childhood APL case harboring a torque teno mini virus/RARA chimeric transcript 25 , and human herpesviruses (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of USP11 in glioma tumorigenesis has been demonstrated by its positive regulation on PML, which is downregulated in majority of cancers and played inhibiting cancer role [ 108 , 109 ]. Hsin-Chieh Wu et al [ 33 ] found that USP11 inhibits the occurrence and progression of glioma via deubiquitinating and stabilizing PML.…”
Section: Usp11 In Cancersmentioning
confidence: 99%